Pengaruh Motivasi Kerja, Manajemen Waktu dan Stres Kerja terhadap Kinerja Pekerja Paruh Waktu yang Berstatus Mahasiswa di Bandar Lampung - Maharani, Fitria; Muhammad, Mahathir; Anggarini, Defia Riski (IPB University, 2024)
Based on the results of interviews with the operational management of Angguran Cafe in Bandar Lampung, they expressed concerns about students who work part-time, where working time conflicts and overhelmed which makes the performance of part-time students decrease. This research investigates how part-time students in Bandar Lampung work, with particular attention to work-related stress, time management, and motivation. This study used quantitative methodologies, and 85 samples of part-time student workers in Bandar Lampung were used to gather data using questionnaires. Descriptive analysis and multiple linear regression analysis were used to analyze the data from the questionnaire. The findings indicated that performance was positively impacted by work motivation and time management, but not significantly by work stress.